Hubungan Tindakan Perataan Laba dengan Reaksi Pasar atas Pengumuman Informasi Laba Perusahaan yang Terdaftar di Bursa Effek Jakarta - Prihat Assih; Gudono Gudono (The Indonesian Journal of Accounting Research, 2013)
The investor’s attention on net income numbers without regard to the procedures used to generate them, has encourage management to carry out earnings management. Includes within earnings management is income smoothing. Income smoothing can be viewed in term of the reduction in earnings variability over a numbers of periods, or within a single period, as the movement toward unexpected level of reported earning.Objective of this study to examine the market reaction on earnings announcement due to the income smoothing. This study examine ninety nine companies which listed in Jakarta Stock  Exchange at least since 1990. Market reaction is measured as cumulative abnormal return five days surrounding the companies’ earnings announcement date.Overall, the result of this study indicate that there is significant market reaction surrounding the companies’ earnings announcement date and these market reaction significantly difference between smoother companies and non-smoother companies.This study is hopes to give contribution to the literature, that income smoothing practice can regard as a signal to better prediction of future earnings by investors and a mean to decrease market reaction on companies’ earnings anouncement.